Mechanical Ottoman: How Robotic Furniture Offers and Withdraws Support - Sirkin, David; Mok, Brian; Yang, Stephen; Ju, Wendy (Hri '15: ACM/IEEE International Conference on Human-Robot Interaction USB Stick, 2015)
This paper describes our approach to designing, developing behaviors for, and exploring the use of, a robotic footstool, which we named the mechanical ottoman. By approaching unsuspecting participants and attempting to get them to place their feet on the footstool, and then later attempting to break the engagement and get people to take their feet down, we sought to understand whether and how motion can be used by non-anthropomorphic robots to engage people in joint action. In several embodied design improvisation sessions, we observed a tension between people perceiving the ottoman as a living being, such as a pet, and simultaneously as a functional object, which requests that they place their feet on it-something they would not ordinarily do with a pet. In a follow-up lab study (N=20), we found that most participants did make use of the footstool, although several chose not to place their feet on it for this reason. We also found that participants who rested their feet understood a brief lift and drop movement as a request to withdraw, and formed detailed notions about the footstool's agenda, ascribing intentions based on its movement alone.